2017
DOI: 10.3390/agronomy7030054
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Lactic Acid-Based Deep Eutectic Solvents (DES) with β-Cyclodextrin: Performance Screening Using Ultrasound-Assisted Extraction of Polyphenols from Selected Native Greek Medicinal Plants

Abstract: Abstract:A series of novel L-lactic acid-based deep eutectic solvents (DES) were tested for polyphenol extraction performance, using organically grown, native Greek medicinal plants. The extractions were ultrasonically-assisted and the effect of the addition of β-cyclodextrin (β-CD) as extraction booster was also tested, at a concentration of 1.5% (w/v). The estimation of total polyphenol yield (Y TP ) suggested that DES composed of L-lactic acid and nicotinamide and L-lactic acid and L-alanine, both at a mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…When the above-mentioned optimal conditions were applied, the total average concentrations of anthocyanins and phenolic compounds were 33.02 mg g −1 and 50.26 mg g −1 , respectively. Similar results were reported by other authors in some vegetable matrices [8,56]. It can be observed that the main phenolic compounds that are present in maqui berries are anthocyanins, unlike many other berries that have less anthocyanin content in comparison with the total phenolic compounds.…”
Section: Optimal Conditionssupporting
confidence: 90%
“…When the above-mentioned optimal conditions were applied, the total average concentrations of anthocyanins and phenolic compounds were 33.02 mg g −1 and 50.26 mg g −1 , respectively. Similar results were reported by other authors in some vegetable matrices [8,56]. It can be observed that the main phenolic compounds that are present in maqui berries are anthocyanins, unlike many other berries that have less anthocyanin content in comparison with the total phenolic compounds.…”
Section: Optimal Conditionssupporting
confidence: 90%
“…mol ) The use of nicotinamide as HBA in L-lactic acid-based DES has been recently reported for the first time [24]; however, the use of glycerol as HBD in combination with nicotinamide as HBA, to the best of the authors' knowledge, is heretofore unreported. When designing a DES, the role of R D/A mol in the polyphenol extraction performance is salient [19,25], and therefore, an initial screening of DES with varying R D/A mol was deemed essential in identifying the highest-performing combination.…”
Section: Des Synthesis and Examination Of Hbd: Hba Molar Ratio (R D/amentioning
confidence: 95%
“…Other additives can be added to assist the extraction of a substance or any other action, however, similarly to the ternary systems, any addition may promote or hamper an extraction, depending on the target. An example by Georgantzi et al [47] shows that the addition of β-cyclodextrin alters the extractability of select flavonoids depending on the selected DES, benefiting one but worsening the other, with varying levels of significance based on the miscellaneous parameters of the extraction.…”
Section: Des As Additives or Additives To Desmentioning
confidence: 99%